Survey of noncontrolled medication misuse patterns - Amelia Slane, PharmD; Sophie Robert, BPharm, PharmD, BCPP; Christine Rarrick, PharmD, MBA, BCPS, BCPP; Erin Weeda, PharmD, BCPS (American Association of Psychiatric Pharmacists, 2022)
Introduction: The abuse potential of opioids and other controlled substances is well-known; however, reports of noncontrolled prescription medication (NCPM) misuse deserves further attention. Whereas several studies investigate patterns, motivations, and biochemical mechanisms underlying the misuse potential of NCPM, the clinical significance of NCPM misuse is not well-understood. The primary objectives of this project were to identify prescriber perceptions of NCPM misuse and evaluate patient reported patterns of misuse through survey responses. Methods: Adult patients admitted to psychiatry services and prescribers working in psychiatry or on a general medicine service during the study time frame were invited to participate. Surveys were collected anonymously for both patients and prescribers. Results: NCPM misuse was reported by 38.4% of patients. Trazodone (35%) and quetiapine (30%) were most commonly reported as being misused. Opioid (24.1% vs 4.3%; P = .023) and cannabis use disorders (13.8% vs 0%; P = .019) were reported more frequently in patients who misuse NCPM, whereas no difference was seen for other SUDs (P > .05). There was no difference between psychiatric and general medicine prescribers regarding familiarity with NCPM misuse (n = 21 [87.5%] vs n = 13 [81.3%]; P = .668). Discussion: High rates of NCPM misuse were seen in this patient population. Our findings confirm previous reports of quetiapine misuse and also reveal that trazodone is frequently misused. Based on the observations in this study, the misuse of NCPM is identified as prevalent and noteworthy at our institution, warranting provider education and future studies.